Redesain KMS Digital Ramah Lansia Untuk Penguatan Peran Kader Posyandu Di Desa Lebakwangi - Satria Mandala; Ledya Novamizanti; Endro Ariyanto (CV. Multi Kreasi Media, 2026)
This community service program was designed to improve the user experience of KMS Digital in posyandu services in Lebakwangi Village, Arjasari Subdistrict, Bandung Regency. The activity continued the previous implementation of KMS Digital as a digital tool for recording and monitoring toddler growth. During early use, several cadres reported that the application was not yet fully convenient, especially for older cadres. The main obstacles were related to a relatively long workflow, an interface that still needed clearer visual organization, and navigation that was not yet fully aligned with the daily practices of posyandu users. Based on this feedback, the 2026 activity placed usability at the center of the improvement process. The work included reorganizing the interface, simplifying the recording flow, strengthening data validation and reporting, and providing direct assistance to users. The stages consisted of reviewing the existing application, collecting user feedback, improving key features, conducting socialization, assisting users, and evaluating partner satisfaction. The revised components included the landing page, cadre dashboard, toddler detail page, parent list, monthly report, and health worker workspace. The socialization activity was held on June 19, 2026, in Lebakwangi Village and involved 24 participants. The questionnaire results showed that 72.50% of responses were in the agree category and 24.17% were in the strongly agree category. Together, these responses reached 96.67%, indicating strong acceptance from the partner community without any rejection. The results suggest that improving KMS Digital based on user needs can increase cadres acceptance of digital systems. Therefore, posyandu digitalization should not be viewed merely as the provision of an application, but as a process of aligning technology with the capacity and field conditions of users. A more elderly-friendly KMS Digital is expected to support more practical recording, monitoring, and reporting of toddler growth.